פשט (x-2) / (x ^ 2 + 6x + 9) - (x + 2) / (2x ^ 2-18)?

פשט (x-2) / (x ^ 2 + 6x + 9) - (x + 2) / (2x ^ 2-18)?
Anonim

תשובה:

# (x ^ 2-15x + 6) / (2 (x-3) (x + 3) ^ 2) #

הסבר:

# x ^ 2 + 6x + 9 = (x + 3) (x + 3) = (x + 3) ^ 2 #

# 2x ^ 2-18 = 2 (x ^ 2-9) = 2 (x-3) (x + 3) #

הפרש של 2 ריבועים # (a-b) (a + b) = a ^ 2-b ^ 2 #

# (x-2) / (x + 3) ^ 2- (x + 2) / (2 (x-3) (x + 3)

הכפל על ידי # 2 (x-3) (x + 3) ^ 2 #

= # (x-2) (x-2) (2) (x-3) - (x + 2) (x + 3)

הרחב את הסוגריים

= # (2 (x ^ 2-5x + 6) - (x ^ 2 + 5x + 6)) / (2 x-3) (x + 3) ^ 2) # #

הרחב עוד יותר את הסוגריים

= # (2x ^ 2-10x + 12-x ^ 2-5x-6) / (2 x-3) (x + 3) ^ 2) # #

לפשט

= # (x ^ 2-15x + 6) / (2 (x-3) (x + 3) ^ 2) #